TRADITION AS AN INITIATOR OF RURAL TOURISM DESTINATIONS DEVELOPMENT - Antić, Aleksandar; Vujko, Aleksandra; Gajić, Tamara (International Journal of Economic Practice and Policy, 2016)
Rural tourism is a form of tourism that best illustrates the importance of tradition in the development of tourist destinations. Music, dance, clothing, culinary specialties of local cuisine, unique natural beauty and the very mentality and hospitality of people in rural areas, represent some of the factors that influence the tourist’s consciousness when choosing this type of holiday. The research is focused on the main hypothesis that the tradition is an initiator of rural tourism destinations development. Furthermore, this would imply positive effects in the field of tourism and economy in general and the economy of the region. The goal of the paper is to show the importance of tradition in the cultural identity of rural areas and potentials of tradition in the role of initiating rural tourism destinations development. The interview with staff members in Pozarevac Tourism Organization has helped in the SWOT analysis of the observed rural destination. An empirical research is conducted on a random sample of 232 participants in order to highlight the benefits of rural tourism development in Pozarevac and its surrounding area. The data were processed in SPSS program (version 17.0).